Islamic Psychotherapy in Handling the Impact of Online Gambling on Mental Health in the Digital Era - Okta Mahendra; Masyhuri Masyuri; Yuslenita Muda (CV. Rayyan Dwi Bharata, 2024)
This article aims to find out in depth about Islamic psychotherapy, online gambling, the factors that influence online gambling, the negative impact of online gambling on mental health, and its potential application in dealing with this problem. In the current digital era, advances in information and communication technology have changed many aspects of human life. One such threat is the increase in online gambling practices, which can have a negative impact on mental health. This research method uses a type or approach in the form of library research. The results found that in dealing with these challenges, the Islamic psychotherapy approach offers solutions that are holistic and in line with the spiritual and cultural values of society. This approach aims to help individuals overcome psychological problems by strengthening spiritual awareness, increasing faith, and improving relationships with God, oneself, and fellow humans.